Saudi faculty online assessment experience: Evidence from the COVID-19 era - Almuqayteeb, Taghreed Abdulaziz; Mohamed, Wessam (Journal of Education and e-Learning Research, 2024)
E-learning has taken the lead over face-to-face instruction in higher education as a response to the COVID-19 pandemic. This shift forced faculty members to adapt to new roles and responsibilities to design and apply online instruction and assessments that require specific skills. This research aims to examine faculty experiences with online assessments during the COVID-19 pandemic at Imam Abdulrahman bin Faisal University (IAU). We used the quantitative study method to analyze faculty experience with online assessment practices during the pandemic using a structured questionnaire composed of 24 items to assess five main areas: faculty awareness, faculty satisfaction, challenges, best practices and suggestions for improvement. This study included one hundred and fifty-five faculty members between September and December 2020. The data obtained were analyzed using descriptive statistics including means, standard deviations, frequencies and percentages. Findings demonstrated high faculty awareness and satisfaction with IAU online assessment practices. However, they expressed they were challenged by their need to receive more faculty development programs on using online assessment and accurately assessing learning outcomes. Moreover, participants pointed out several best practices such as investing in learning management system tools for assessment and student feedback provision. Finally, the primary recommendation for enhancing online assessments was to provide faculty access to professional development training programmes. This study provides a reference for future research on student-centered online learning and assessment practices, accreditation of online assessment practices and strategies for assessing and compensating for learning loss during the pandemic.